Utilising scenario-based simulation modelling to optimise aircraft inspection scheduling. (26th August 2021) - Islam, Rubayat; Wang, Shengyong; Ling, Chen
The main aim of this paper is to generate different visual simulation modelling scenarios for performing inspection operations on different Federal Aviation Administration facilities. Different combinations of aircraft and routes are scheduled to design different scenarios for performing inspections. For assigning aircraft into the model, a study of FAA current fleet composition is made. To make the model robust, probabilistic distribution is introduced into the modelling approach. For every modelling approach or scenario, various numbers of experiments with thousands of replications are scheduled to generate a maximum, minimum and average number of inspections over a year that can be performed through that modelling approach. Furthermore, a comparison of the different modelling approaches is made based on the number of inspections made by each model over a year.